Analisis Kemampuan Berhitung Anak Autis melalui Penggunaan Puzzle Angka di Permata Diakonia - Hotmaida Sitopu; Natalina Purba; Hetdy Sitio (Piramida Akademi, 2026)
Numeracy is a fundamental competency essential for every child, including children with autism. In learning, autistic children tend to have difficulty understanding number concepts, especially when the material is presented abstractly. Therefore, concrete and engaging learning media are needed to facilitate comprehension. This study aims to assess the numeracy skills of autistic children through the use of number puzzle s in learning activities. This study used a qualitative approach with a case study approach. The research subjects consisted of one autistic child and one teacher as informants. Data collection was conducted through observation, interviews, and documentation. The data obtained were then analyzed using qualitative data analysis techniques. The results showed an increase in numeracy skills in children, characterized by the ability to recognize numbers, name numbers, and arrange number sequences, although this was not yet consistent. The use of number puzzle s increased children's engagement and attention and helped them understand number concepts more concretely. The teacher's role in providing guidance and support also contributed to the success of the learning process. Future research is recommended to involve more subjects and develop a variety of learning media to provide more comprehensive results.